On the photovoltaic effect asymmetry in ferroelectrics. (8th March 2023) - Semak, S; Kapustianyk, V; Eliyashevskyy, Yu; Bovgyra, O; Kovalenko, M; Mostovoi, U; Doudin, B; Kundys, B
Abstract: Despite symmetrical polarization, the magnitude of a light-induced voltage is known to be asymmetric with respect to poling sign in many photovoltaic (PV) ferroelectrics (FEs). This asymmetry remains unclear and is often attributed to extrinsic effects. We show here for the first time that such an asymmetry can be intrinsic, steaming from the superposition of asymmetries of internal FE bias and electro-piezo-strictive deformation. This hypothesis is confirmed by the observed decrease of PV asymmetry for smaller FE bias. Moreover, the both PV effect and remanent polarization are found to increase under vacuum-induced expansion and to decrease for gas-induced compression, with tens percents tunability. The change in cations positions under pressure is analysed through the first-principle density functional theory calculations. The reported properties provide key insight for FE-based solar elements optimization.